1998
DOI: 10.1177/070674379804300107
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Posttraumatic Stress Disorder in an Adolescent Inpatient Unit

Abstract: PTSD occurs frequently in adolescent inpatients and is commonly comorbid with other diagnostic presentations. These findings may affect the management of PTSD and prognosis for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
6

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 15 publications
2
37
0
6
Order By: Relevance
“…Quite frequently, patients avoid stimuli associated with the traumatic event, associated with the compromise of their daily activities. 36,37 Patients avoid talking about the event, which seemingly worsens the symptoms, as often occurs in all anxiety disorders. Younger children have difficulty understanding the event clearly and talking about it.…”
Section: Posttraumatic Stress Disorder (Ptsd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Quite frequently, patients avoid stimuli associated with the traumatic event, associated with the compromise of their daily activities. 36,37 Patients avoid talking about the event, which seemingly worsens the symptoms, as often occurs in all anxiety disorders. Younger children have difficulty understanding the event clearly and talking about it.…”
Section: Posttraumatic Stress Disorder (Ptsd)mentioning
confidence: 99%
“…PTSD is regarded as a risk factor for the later development of psychiatric diseases. 36,37 PTSD is the intense fear, feeling of powerlessness or horror due to the exposure to an extreme trauma, such as life threat or sexual assault. The probability of developing PTSD is reliant on the severity, length, and time of exposure of the individual to the traumatic event.…”
Section: Posttraumatic Stress Disorder (Ptsd)mentioning
confidence: 99%
“…Researchers have also consistently reported that PTSD is associated with various psychiatric conditions (10). Axis I disorders that are frequently comorbid with PTSD include depression (11,12), anxiety disorders (13,14), substance use disorders (15), and eating and somatization disorders (16). Comorbid Axis II disorders, including borderline personality disorder, have also been noted (17).…”
mentioning
confidence: 99%
“…4,8 The rates of respiratory illness are also higher than expected among some psychiatric patient populations, compared to the general population. 9,10 As data from clinical settings are limited in their generalizability to the community since effect sizes may be skewed by selection into treatment bias, it is important to also examine this relationship using community-based data. Epidemiologic studies 11,12 in adults have shown that panic disorder co-occurs with asthma more frequently than would be expected by chance.…”
mentioning
confidence: 99%